«Novel without World» and other Techniques for the Fading of the Self in Macedonio Fernández - Vivas Hurtado, Selnich; Gaviria Echavarría, María Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In the novel Museo de la novela de la Eterna [ Museum of Eterna›s Novel (The First Good Novel )] and through the use of the concepts of « Belarte » [Belle art] and «Humorism», Macedonio Fernández aims to create an experimental novel based on the doubt and fading of the Self. Processes of massification and industrialization in the Buenos Aires of the late nineteenth and early twentieth centuries resulted, among others, in the fragmentation and alienation of the subject. In such a context, and through the rise of avant-garde movements, the arts, and specifically literature, set out to find ways to name this transformed environment. In this context, Macedonio starts to plan his novel, a novel that doesn ́t begin, and that theorizes about its own construction; a novel about the illogical, that will liberate the subject. This paper will explore how this novel develops the liberation of the self in the light of «Belarte» and «Humorism», and how Macedonio ́s legacy to literature is a novel of failure